Laser Sintering with Plastics : Technology, Processes, and Materials - Schmid, Manfred, 1958-, author 629615; ScienceDirect (Online service) 7722 (Cincinnati : Hanser, 2018)
Laser Sintering (LS) with plastics is one of the most promising additive manufacturing technologies: it is currently regarded as the process most likely in the future to permanently cross the border between prototyping and the production of functional parts. This step is challenging because it means that the technology must meet certain requirements that are also valid for traditional and established production processes. Only by succeeding at this step can a wide industry acceptance of LS be expected in the future.